The Kajian Experimental Karakterisasi Sifat Mekanik Hasil Pengelasan FCAW Material JIS G3106 Grade SM 490 YB: Kajian Experimental Karakterisasi Sifat Mekanik Hasil Pengelasan FCAW Material JIS G3106 Grade SM 490 YB - DENDI, DENDI HANDIMAN (KILAT, 2024)
The results of the study of the mechanical properties of low carbon steel mechanical characteristics in shearing, plasma and oxyfuel cutting technologies to determine the application and preparation of the workpiece side without machining and subsequent piecing will be discussed in this study. The results show that the lowest hardness is at shearing cuts, while the highest is obtained by plasma cutting and oxyfuel. The depth of the heat-affected zone (HAZ) varies from 1 to 4 mm for plasma and oxyfuel depending on the type of steel and cutting. The tensile strength of FCAW welding results between shearing, plasma and oxyfuel cutting technologies has a yield strength difference of around 5.6 N / mm2 and the highest impact yield on plasma cutting results is 81.3 joules.